High rate of burnout among residents under standardized residency training in a tertiary teaching hospital of middle China: Results from a cross-sectional survey. Issue 27 (2nd July 2020) - Geng, Hongfang; Tan, Fang; Deng, Yingqing; Lai, Lifei; Zhang, Jiaqiang; Wu, Zhenlong; Liu, Peibin; Zhu, Qianqian
Abstract : Abstract: Burnout has been commonly observed in health care workers. Though research has been conducted involving burnout among doctors in China, few studies have focused on residents during standardized residency training (SRT). The professional status of the residents during SRT remains largely unclear. The present study was conducted in order to clarify the prevalence and potential risk factors of burnout in residents during SRT. An electronic questionnaire comprised 2 parts. The first part was designed to collect some basic characteristic information. Maslach Burnout Inventory-Human Services Survey was included in the second part. As many as 71.05% residents had at least 1 scale of burnout. Emotional exhaustion (EE) was found in 55.6% residents, depersonalization (DP) in 29.7% and reduced personal accomplishment (RPA) in 41.6%. Being older than 27, senior SRT year, working time more than 60 hours per week and poor sleeping quality was independently associated with at least on scale of burnout. Being unable to receive timely supervisor support significantly increased the probability of DP and EE. Not having friends at work or feeling cared for by the hospital were independently related to all 3 symptoms of burnout as well as overall burnout. Burnout rate is high in residents under SRT from middle part of China. Organizational, professional, and social support was demonstrated critical by the potential roles in protecting against burnout. Residents with burnout were prone to considering turnover. Strategies for managing burnout related factors among residents should be focused in future studies.